Neurodevelopmental outcomes in children with isolated congenital diaphragmatic hernia: A systematic review and meta‐analysis. (21st March 2021) - Van der Veeken, Lennart; Vergote, Simen; Kunpalin, Yada; Kristensen, Karl; Deprest, Jan; Bruschettini, Matteo
Abstract: Background : Congenital diaphragmatic hernia (CDH) reportedly has neurologic consequences in childhood however little is known about the impact in isolated CDH. Aims: Herein we aimed to describe the risk of neurodevelopmental complications in children born with isolated CDH. Materials & Methods: We systematically reviewed literature for reports on the neurological outcome of infants born with isolated CDH. The primary outcome was neurodevelopmental delay. Secondary outcomes included, motor skills, intelligence, vision, hearing, language and behavior abnormalities. Results: Thirteen out of 87 (15%) studies reported on isolated CDH, including 2624 out of 24, 146 children. Neurodevelopmental delay was investigated in four studies and found to be present in 16% (3‐34%) of children. This was mainly attributed to motor problems in 13% (2‐30%), whereas cognitive dysfunction only in 5% (0‐20%) and hearing in 3% (1‐7%). One study assessed the effect of fetal surgery. When both isolated and non‐isolated children were included, these numbers were higher. Discussion: This systematic review demonstrates that only a minority of studies focused on isolated CDH, with neurodevelopmental delay present in 16% of children born with CDH. Conclusion: To accurately counsel patients, more research should focus on isolated CDH cases and examine children that underwent fetal surgery. Highlights: What's already known about this topic? Children born with congenital diaphragmatic hernia (CDH) are at increased risk for neurodevelopmental delay Most published data reports on combined isolated and nonisolated CDH cases What does this review add? This is the first review examining the impact of isolated CDH This can be used when counseling CDH patients that qualify for fetal surgery on the neurologic outcome